Preservation of Pancreatic Function Should Not Be Disregarded When Performing Pancreatectomies for Pancreatoblastoma in Children - Traian Dumitrascu (MDPI AG, 2024)
Complete surgical resection in the context of a multimodal approach has been associated with excellent long-term survival in children diagnosed with pancreatoblastoma (PB). Traditionally, curative intent surgery for PB implies standard pancreatic resections such as pancreaticoduodenectomies and distal pancreatectomies with splenectomies, surgical procedures that may lead to significant long-term pancreatic functional deficiencies. Postoperative pancreatic functional deficiencies are particularly interesting to children because they may interfere with their development, considering their long life expectancy and the significant role of pancreatic functions in their nutritional status and growth. Thus, organ-sparing pancreatectomies, such as spleen-preserving distal pancreatectomies and central pancreatectomies, are emerging in specific tumoral pathologies in children. However, data about organ-sparing pancreatectomies' potential role in curative-intent PB surgery in children are scarce. Based on the literature data, the current review aims to present the early and late outcomes of pancreatectomies in children (including long-term deficiencies and their potential impact on the development and quality of life), particularly for PB, and further explore the potential role of organ-sparing pancreatectomies for PB. Organ-sparing pancreatectomies are associated with better long-term pancreatic functional outcomes, particularly central pancreatectomies, and have a reduced impact on children's development and quality of life without jeopardizing their oncological safety. The long-term preservation of pancreatic functions should not be disregarded when performing pancreatectomies for PB in children. A subset of patients with PB might benefit from organ-sparing pancreatectomies, particularly from central pancreatectomies, with the same oncological results as standard pancreatectomies but with significantly less impact on long-term functional outcomes.